Preparation method and application of oxygen-doped cobalt phosphide / carbon nanotube composite material
By using oxygen-doped cobalt phosphide/carbon nanotube composite as a catalyst, the shuttle effect and lithium dendrites in lithium sulfur batteries are solved, and the electrochemical performance of lithium sulfur batteries is improved and the conversion of polysulfides is accelerated.
Patent Information
- Application Number
- CN202310038872.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-01-13
AI Technical Summary
Lithium-sulfur batteries have serious shuttle effects and lithium dendrites problems, which lead to their inability to commercially produce them.
The oxygen-doped cobalt phosphide/carbon nanotube composite material is used as a catalyst to oxygen dopant CoP by calcining in a tube furnace to generate cobalt metaphosphate, increasing the active site of adsorbed polysulfide, thereby accelerating its conversion. The material is coated on the separator to prepare a functional separator for use in lithium-sulfur batteries.
It significantly improves the electrochemical performance of lithium-sulfur batteries, effectively inhibits the shuttle effect of polysulfides, and improves specific capacity and cycle stability.
Smart Images

Figure CN115986320B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to lithium-sulfur battery technology, and in particular to a preparation method and application of an oxygen-doped cobalt phosphide / carbon nanotube composite material. Background Art
[0002] With the development of new energy vehicles, their driving range and battery cost have received widespread attention. The current mainstream new energy vehicle has a driving range of about 600km, and the battery cost is 60,000-80,000 yuan. Lithium-sulfur batteries can make the driving range of new energy vehicles reach more than 1,000km, and the battery cost is 10% of the mainstream lithium battery cost. Compared with current lithium-ion batteries, lithium-sulfur batteries have better performance and less impact on the environment. Due to the abundant sulfur reserves, low price, environmental friendliness and theoretical specific capacity (1675 mAh g -1 ), high energy density (2500 Wh·kg -1 or 2800 Wh·L -1 ), lithium-sulfur batteries have become the focus of researchers. However, lithium-sulfur batteries have serious "shuttle effect" and lithium dendrites, which make them impossible to commercialize. At present, the main method to solve the "shuttle effect" problem is to add catalysts to lithium-sulfur batteries.
[0003] Metal phosphides (CoP, Ni2P, FeP, MoP and Sn4P3, etc.) have outstanding metallic properties. When metal phosphides act as sulfur hosts, they will greatly improve the conductivity of the electrode. In addition, these metal phosphides have strong polarity, so LiPS can be well adsorbed to reduce the impact of the shuttle effect. Ultimately, their excellent catalytic effect can effectively catalyze most chemical reactions. Existing research progress has shown that metal phosphides can promote the conversion of LiPS and increase the rate of electrochemical reactions.
[0004] Because of these obvious advantages, functional metal phosphides are widely used in lithium-sulfur batteries and greatly improve the electrochemical performance. In addition, O-CoP / CNT composites are used as catalysts for lithium-sulfur batteries and coated on polypropylene diaphragms to prepare functionalized diaphragms; O is used to dope CoP / CNT composites with anions to improve the adsorption of CoP / CNT composites on polysulfides and inhibit the shuttle effect, thereby improving the electrochemical performance of lithium-sulfur batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of an oxygen-doped cobalt phosphide / carbon nanotube composite material in view of the deficiencies of the prior art. This preparation method is simple, low-cost, environmentally friendly and safe, and does not need to be completed under closed high-pressure reaction conditions. The material prepared by this method provides more active sites for the adsorption of polysulfides, can accelerate the conversion of polysulfides, and is coated on a diaphragm to prepare a functionalized diaphragm, which can significantly improve the electrochemical performance of lithium-sulfur batteries and effectively inhibit the shuttling of polysulfides.
[0006] The technical solution for achieving the purpose of the present invention is:
[0007] A method for preparing an oxygen-doped cobalt phosphide / carbon nanotube composite material comprises the following steps:
[0008] 1) Preparation of Co3O4 / CNT composite material: Cobalt chloride and carbon nanotubes are dissolved in an aqueous solution, 100 μl of ammonia water is added dropwise, the temperature is adjusted to 60-120°C, and stirred at a low speed for 7-15 hours to grow Co3O4 particles on the surface of the carbon nanotubes. After the reaction is completed, the mixture is washed with ethanol and deionized water, and the mixture is washed 3 times. The washed sample is freeze-dried to obtain a Co3O4 / CNT composite material, wherein the carbon nanotubes are multi-walled carbon nanotubes. The purpose of washing the product is mainly to remove reaction impurities to ensure that a pure product is obtained without being affected by impurities;
[0009] 2) Preparation of CoP / CNT composite material: Anhydrous sodium hypophosphite NaH2PO2 is used as a phosphorus source and placed upstream of a tube furnace. The Co3O4 / CNT material prepared in step 1) is dried and placed downstream of the tube furnace. In an inert protective gas atmosphere, the temperature is raised to 350°C and kept for 2 hours at a heating rate of 5°C / min and a gas flow rate of 60 sccm to obtain a CoP / CNT composite material, wherein the inert atmosphere is argon or nitrogen;
[0010] 3) Preparation of O-CoP / CNT composite material: The CoP / CNT prepared in step 2) is placed in a tubular furnace, heated to 100-400°C in an air atmosphere for 30 minutes for oxygen doping, the heating rate is 5°C / min, the gas flow rate is 60sccm, and cooled to room temperature in an air atmosphere to obtain an O-CoP / CNT composite material, i.e., an oxygen-doped cobalt phosphide / carbon nanotube composite material.
[0011] The ammonia water described in step 1) is an aqueous solution containing 25% to 28% ammonia.
[0012] The mass ratio of Co3O4 / CNT to NaH2PO2 in step 2) is 1:10.
[0013] The O-CoP / CNT modified functional diaphragm is prepared by the oxygen-doped cobalt phosphide / carbon nanotube composite material prepared by the preparation method of the oxygen-doped cobalt phosphide / carbon nanotube composite material. The diaphragm substrate of the functional diaphragm is Celgard2500, and the O-CoP / CNT composite material is coated on the diaphragm substrate.
[0014] The preparation process of the functionalized membrane is as follows: O-CoP / CNT, conductive carbon, a binder and a solvent are dispersed to form a uniform slurry, wherein the mass ratio of O-CoP / CNT, conductive carbon and the binder is 8:1:1; the obtained slurry is uniformly coated on one side of a membrane substrate material by any one of spraying, blade coating or coating roller to form an O-CoP / CNT modified functionalized membrane, and then the coated membrane is vacuum dried at 50-60° C. to obtain an O-CoP / CNT modified functionalized membrane, wherein the conductive carbon is one or more of conductive carbon black, acetylene black, ketjen carbon and activated carbon, the binder is polyvinylidene fluoride PVDF, and the solvent is N-methylpyrrolidone NMP.
[0015] Application of the oxygen-doped cobalt phosphide / carbon nanotube composite material prepared by the above-mentioned preparation method of the oxygen-doped cobalt phosphide / carbon nanotube composite material in lithium-sulfur batteries.
[0016] The process of preparing the above functionalized diaphragm for lithium-sulfur battery is as follows:
[0017] A lithium-sulfur battery was assembled with a sulfur / graphene composite material as the positive electrode, a metal lithium sheet as the negative electrode, a functionalized diaphragm modified with an O-CoP / CNT composite material and an ether electrolyte, wherein one side of the O-CoP / CNT composite material covered on the diaphragm substrate was opposite to the positive electrode sheet, and the other side was opposite to the negative electrode sheet. A 2032-type button cell was prepared in a glove box with a water and oxygen content of less than 0.01 ppm, wherein: the sulfur / graphene composite material was formed by grinding sulfur and graphene in a mass ratio of 9:1 uniformly and calcining them in a tube furnace for 18 hours; the positive electrode sheet was composed of a mixture of sulfur / graphene, conductive carbon black SP, and polyvinylidene fluoride in a mass ratio of 8:1:1; the ether electrolyte was a mixed solution of 1 M lithium bistrifluoromethanesulfonyl imide LiTFSI, dioxolane ether cyclo DOL and ethylene glycol dimethyl ether DME, and 1 wt% lithium nitrate LiNO3.
[0018] Compared with the prior art, this technical solution has the following beneficial effects:
[0019] This technical solution introduces air during calcination in a tubular furnace to oxygen-dope CoP, and generates cobalt metaphosphate on the surface of the oxygen-doped cobalt phosphide / carbon nanotube composite material, which can provide more active sites for the adsorption of polysulfides and accelerate the conversion of polysulfides. The oxygen-doped cobalt phosphide / carbon nanotube composite material is coated on the diaphragm to prepare a functional diaphragm, which can significantly improve the electrochemical performance of lithium-sulfur batteries and effectively inhibit the shuttling of polysulfides.
[0020] 2. The O-CoP / CNT composite material prepared by this technical solution is applied to lithium-sulfur batteries. At a current density of 5C, the lithium-sulfur battery achieves 526.4 mAh·g -1 The specific capacity remains at 961.7 mAh g after 500 cycles at 0.2C. -1 Specific capacity.
[0021] This preparation method is simple, low-cost, environmentally friendly and safe, and does not require closed high-pressure reaction conditions. The material prepared by this method provides more active sites for the adsorption of polysulfides, which can accelerate the conversion of polysulfides. It can be coated on the diaphragm to prepare a functional diaphragm, which can significantly improve the electrochemical performance of lithium-sulfur batteries and effectively inhibit the shuttling of polysulfides. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The X-ray diffraction pattern of Co3O4 / CNT in the embodiment;
[0023] Figure 2 This is the Raman spectrum of Co3O4 / CNT in the embodiment;
[0024] Figure 3 Raman spectra of the CoP / CNT composite material and the O-CoP / CNT composite material in the examples;
[0025] Figure 4 It is a transmission electron microscope image of the O-CoP / CNT composite material in the embodiment;
[0026] Figure 5 The polysulfide adsorption diagram of the CoP / CNT composite material and the O-CoP / CNT composite material in the embodiment;
[0027] Figure 6 The electrochemical performance diagram of lithium-sulfur batteries assembled with different separators in the embodiment;
[0028] Figure 7 The rate performance diagram of lithium-sulfur batteries assembled with different separators in the embodiment;
[0029] Figure 8 This is a cycle performance diagram of lithium-sulfur batteries assembled with different separators in the examples. Implementation
[0030] The content of the present invention is further described below in conjunction with the drawings and embodiments, but the present invention is not limited thereto. Example
[0031] Embodiment 1: A method for preparing an O-CoP / CNT composite material, comprising:
[0032] 1) Preparation of Co3O4 / CNT composite material: 11.897 g of cobalt chloride hexahydrate was dissolved in 50 ml of deionized water to form a uniform solution; 100 mg of hydroxylated carbon nanotubes was added to the above solution, and the suspension was mixed evenly by stirring and ultrasonication; 100 μl of ammonia solution was added dropwise to the suspension and continued to stir evenly; the above solution was placed in an oil bath, the temperature was adjusted to 80°C, and stirred at a low speed for 12 hours until precipitation occurred, that is, Co3O4 particles grew on the surface of the carbon nanotubes; the obtained solution was filtered, and the product was washed 3 times with ethanol and deionized water respectively; the product obtained by filtration was dried by freeze-drying for 24 hours; the dried sample was taken out to obtain a powdered Co3O4 / CNT composite material;
[0033] 2) Preparation of CoP / CNT composite material: Anhydrous sodium hypophosphite was used as a phosphorus source and placed upstream of a tubular furnace, and the dried Co3O4 / CNT composite material was placed downstream of the tubular furnace, wherein the mass ratio of the Co3O4 / CNT composite material to anhydrous sodium hypophosphite was 1:10. Under an inert protective gas atmosphere, the temperature was raised to 350°C and kept for 2 hours for phosphating, the heating rate was 5°C min, the gas flow rate was 60 sccm, and after cooling to room temperature, a CoP / CNT composite material was obtained;
[0034] 3) Preparation of O-CoP / CNT composite material: The CoP / CNT composite material prepared in step 2) was placed in a tubular furnace, heated to 300°C in an air atmosphere and kept for 30 minutes for oxygen doping, with a heating rate of 5°C / min and a gas flow rate of 60 sccm to obtain an O-CoP / CNT composite material.
[0035] The X-ray diffraction patterns of the materials prepared above were tested, such as Figure 1As shown in the figure, no other impurity peaks except Co3O4 and CNT were observed in the XRD diffraction peaks of the Co3O4 / CNT composite material, indicating that a pure Co3O4 / CNT composite material was prepared with good crystallinity. From the XRD diagram of the CoP / CNT composite material, it can be seen that after the Co3O4 / CNT composite material was phosphated, the diffraction peak of Co3O4 completely disappeared, and only the diffraction peaks of CoP and CNT could be observed, indicating that Co3O4 was successfully phosphated into cobalt phosphide. In addition, no other impurities were detected. With further heat treatment in an air atmosphere, the diffraction peaks of the O-CoP / CNT composite material and the CoP / CNT composite material coincided, so oxygen doping had no obvious effect on the bulk structure of CoP.
[0036] Raman characterization of the composites before and after oxygen doping was performed, e.g. Figure 3 As shown, the CoP / CNT composite material has a -1 and ~269.5cm -1 There are two peaks at ~682cm, which correspond to the active mode F2g generated by natural oxidation in the oxide lattice and the characteristic Eg active mode in the CoP lattice. After annealing in air, the Raman spectrum of the O-CoP / CNT composite material is ~682cm -1 and ~1153cm -1 Two peaks appeared at , which correspond to the active modes A1g and ν3 (PO3) antisymmetric stretching vibrations in the oxide lattice. The above results show that the CoP surface structure exists in the form of oxygen doping;
[0037] The prepared materials were characterized by TEM. Figure 4 As shown, the nanoparticles of the O-CoP / CNT composite material are distributed around the carbon nanotubes to form a three-dimensional network structure, which is beneficial to accelerate the charge transfer in the electrochemical process. Due to O doping, many obvious holes can be found;
[0038] The same mass of CNT, CoP / CNT and O-CoP / CNT were added into 4 ml of 2 mM Li2S6 solution for polysulfide adsorption experiments. Figure 5 As shown, the color of the Li2S6 solution with the addition of O-CoP / CNT faded significantly after standing for 10 min, while the Li2S6 solution with the addition of CNT remained yellow, and the Li2S6 solution with CoP / CNT only faded slightly.
[0039] Preparation of functionalized diaphragm modified with O-CoP / CNT composite material: Disperse the prepared O-CoP / CNT composite material, conductive carbon, binder and solvent to form a uniform slurry, wherein the mass ratio of O-CoP / CNT composite material, conductive carbon and binder is 8:1:1; Use a scraper to evenly coat the obtained slurry on one side of the diaphragm matrix material to form a functionalized diaphragm modified with O-CoP / CNT composite material; Vacuum dry the coated diaphragm at 50°C, and cool to room temperature to obtain a functionalized diaphragm modified with O-CoP / CNT.
[0040] Assembly of functionalized separator lithium-sulfur battery modified with O-CoP / CNT composite material: A lithium-sulfur battery was assembled with sulfur / graphene composite material as positive electrode, metal lithium sheet as negative electrode, O-CoP / CNT modified functionalized separator (polypropylene Celgard 2500) and DOL / DME (V:V=1:1) ether electrolyte containing 1MLiTFSI and 1 wt% LiNO3, wherein one side of the O-CoP / CNT composite material covered on the separator substrate was opposite to the positive electrode sheet, and the other side was opposite to the negative electrode sheet. A 2032-type button cell was prepared in a glove box with a water and oxygen content of less than 0.1 ppm, wherein the sulfur / graphene composite material was formed by grinding sulfur and graphene in a mass ratio of 9:1 evenly and calcining in a tubular furnace for 18 hours, and the positive electrode sheet was composed of a mixture of sulfur / graphene, conductive carbon black SP, and polyvinylidene fluoride in a mass ratio of 8:1:1.
[0041] Figure 6 The electrochemical performance diagram of lithium-sulfur batteries assembled with different materials coated on the separator shows the typical two-step discharge and one-step charge behavior of the sulfur positive electrode. From the O-CoP / CNT curve, it can be seen that the two cathode peaks at ~2.3V and ~2.0V are attributed to the formation of polysulfide intermediates and product Li2S, and the anode peak at ~2.1V corresponds to its oxidation process. By comparison, it is found that the redox current of the O-CoP / CNT coated separator battery is higher and has a narrower current peak, and the polarization is relatively small, which proves that O-CoP / CNT has a faster electrochemical conversion rate.
[0042] Figure 7 The rate performance of lithium-sulfur batteries assembled by coating different materials on the separator is Figure 7 It can be seen that the specific capacity of the first discharge of O-CoP / CNT at the corresponding rate is higher than that of CoP / CNT composites, and the O-CoP / CNT composite can reach 526.4 mAh·g at a rate of 5C. -1, has good rate performance. The improvement in performance may be attributed to the further improvement of the anchoring effect of O-doped CoP on polysulfides. At the same time, the formed Co-O bonds can promote the redox conversion rate of polysulfides, accelerate the redox reaction kinetics of lithium polysulfide in lithium-sulfur batteries, and inhibit the "shuttle effect".
[0043] Figure 8 The cycling performance of lithium-sulfur batteries assembled with different materials coated on the separator is Figure 8 It can be seen that the first discharge capacity of O-CoP / CNT at 0.2 C is 1280.8 mAh·g -1 Even after 500 cycles, the capacity remains at 961.7 mAh g -1 ,As can be seen from the figure, the O-CoP / CNT composite material has the best cycle performance, and its discharge specific capacity has been significantly improved.
[0044] Embodiment 2: A method for preparing an O-CoP / CNT composite material, comprising:
[0045] 1) Preparation of Co3O4 / CNT composites:
[0046] 11.897 g of cobalt chloride hexahydrate was dissolved in 50 ml of deionized water to form a uniform solution; 100 mg of hydroxylated carbon nanotubes was added to the above solution, and the suspension was mixed evenly by stirring and ultrasonication; 100 μl of ammonia solution was added dropwise to the suspension, and the stirring was continued to be evenly stirred; the above solution was placed in an oil bath, the temperature was adjusted to 60°C, and stirred at a low speed for 16 hours until precipitation occurred, that is, Co3O4 particles grew on the surface of the carbon nanotubes; the obtained solution was filtered, and the product was washed 3 times with ethanol and deionized water respectively; the product obtained by filtration was dried by freeze drying for 24 hours; the dried sample was taken out to obtain a powdered Co3O4 / CNT composite material;
[0047] 2) Preparation of CoP / CNT composite material: Anhydrous sodium hypophosphite was used as a phosphorus source and placed upstream of a tubular furnace, and the dried Co3O4 / CNT composite material was placed downstream of the tubular furnace, wherein the mass ratio of the Co3O4 / CNT composite material to anhydrous sodium hypophosphite was 1:10, and the temperature was raised to 350°C for 2 hours under an inert protective gas atmosphere for phosphating, the heating rate was 5°C / min, the gas flow rate was 60 sccm, and after cooling to room temperature, a CoP / CNT composite material was obtained;
[0048] 3) Preparation of O-CoP / CNT composite material: The CoP / CNT composite material prepared in step 2) was placed in a tubular furnace, heated to 100°C in an air atmosphere for 30 minutes for oxygen doping, with a heating rate of 5°C / min and a gas flow rate of 60 sccm to obtain an O-CoP / CNT composite material.
[0049] Embodiment 3: A method for preparing an O-CoP / CNT composite material, comprising:
[0050] 1) Preparation of Co3O4 / CNT composite material: 11.897 g of cobalt chloride hexahydrate was dissolved in 50 ml of deionized water to form a uniform solution; 100 mg of hydroxylated carbon nanotubes was added to the above solution, and the suspension was mixed evenly by stirring and ultrasonication; 100 μl of ammonia solution was added dropwise to the suspension and continued to stir evenly; the above solution was placed in an oil bath, the temperature was adjusted to 100°C, and stirred at a low speed for 10 hours until precipitation occurred, that is, Co3O4 particles grew on the surface of the carbon nanotubes; the obtained solution was filtered, and the product was washed 3 times with ethanol and deionized water respectively; the product obtained by filtration was dried by freeze-drying for 24 hours; the dried sample was taken out to obtain a powdered Co3O4 / CNT composite material;
[0051] 2) Preparation of CoP / CNT composite material: Anhydrous sodium hypophosphite was used as a phosphorus source and placed upstream of a tubular furnace, and the dried Co3O4 / CNT composite material was placed downstream of the tubular furnace, wherein the mass ratio of the Co3O4 / CNT composite material to anhydrous sodium hypophosphite was 1:10, and the temperature was raised to 350°C for 2 hours under an inert protective gas atmosphere for phosphating, the heating rate was 5°C / min, the gas flow rate was 60 sccm, and after cooling to room temperature, a CoP / CNT composite material was obtained;
[0052] 3) Preparation of O-CoP / CNT composite material: The CoP / CNT composite material prepared in step 2) was placed in a tubular furnace, heated to 200°C in an air atmosphere and kept for 30 minutes for oxygen doping, with a heating rate of 5°C / min and a gas flow rate of 60 sccm to obtain an O-CoP / CNT composite material.
[0053] Embodiment 4: A method for preparing an O-CoP / CNT composite material, comprising:
[0054] 1) Preparation of Co3O4 / CNT composite material: 11.897 g of cobalt chloride hexahydrate was dissolved in 50 ml of deionized water to form a uniform solution; 100 mg of hydroxylated carbon nanotubes was added to the above solution, and the suspension was mixed evenly by stirring and ultrasonication; 100 μl of ammonia solution was added dropwise to the suspension and continued to stir evenly; the above solution was placed in an oil bath, the temperature was adjusted to 120°C, and stirred at a low speed for 7 hours until precipitation occurred, that is, Co3O4 particles grew on the surface of the carbon nanotubes; the obtained solution was filtered, and the product was washed 3 times with ethanol and deionized water respectively; the product obtained by filtration was dried by freeze drying for 24 hours; the dried sample was taken out to obtain a powdered Co3O4 / CNT composite material;
[0055] 2) Preparation of CoP / CNT composite material: Anhydrous sodium hypophosphite was used as a phosphorus source and placed upstream of a tubular furnace, and the dried Co3O4 / CNT composite material was placed downstream of the tubular furnace, wherein the mass ratio of the Co3O4 / CNT composite material to anhydrous sodium hypophosphite was 1:10, and the temperature was raised to 350°C for 2 hours under an inert protective gas atmosphere for phosphating, the heating rate was 5°C / min, the gas flow rate was 60 sccm, and after cooling to room temperature, a CoP / CNT composite material was obtained;
[0056] 3) Preparation of O-CoP / CNT composite material: The CoP / CNT composite material prepared in step 2) was placed in a tubular furnace, heated to 400°C in an air atmosphere and kept for 30 minutes for oxygen doping, with a heating rate of 5°C / min and a gas flow rate of 60 sccm to obtain an O-CoP / CNT composite material.
Claims
1. A method for preparing an oxygen-doped cobalt phosphide / carbon nanotube composite material, characterized in that: The steps include: 1) Preparation of Co3O4 / CNT composite material: Cobalt chloride and carbon nanotubes were dissolved in an aqueous solution, 100 μl of ammonia water was added dropwise, the temperature was adjusted to 60-120°C, and stirred at a low speed for 7-15 hours to grow Co3O4 particles on the surface of the carbon nanotubes. After the reaction, the mixture was washed with ethanol and deionized water for 3 times, and the washed sample was freeze-dried to obtain a Co3O4 / CNT composite material, wherein the carbon nanotubes are multi-walled carbon nanotubes; 2) Preparation of CoP / CNT composite material: Anhydrous sodium hypophosphite NaH2PO2 is used as a phosphorus source and placed upstream of a tube furnace. The Co3O4 / CNT material prepared in step 1) is dried and placed downstream of the tube furnace. In an inert protective gas atmosphere, the temperature is raised to 350°C and kept for 2 hours at a heating rate of 5°C / min and a gas flow rate of 60 sccm to obtain a CoP / CNT composite material, wherein the inert atmosphere is argon or nitrogen; 3) Preparation of O-CoP / CNT composite material: The CoP / CNT prepared in step 2) is placed in a tubular furnace, heated to 100-400°C in an air atmosphere for 30 minutes for oxygen doping, the heating rate is 5°C / min, the gas flow rate is 60 sccm, and cooled to room temperature in an air atmosphere to obtain an O-CoP / CNT composite material, i.e., an oxygen-doped cobalt phosphide / carbon nanotube composite material.
2. The method for preparing the oxygen-doped cobalt phosphide / carbon nanotube composite material according to claim 1, characterized in that: The ammonia water described in step 1) is an aqueous solution containing 25% to 28% ammonia.
3. The method for preparing the oxygen-doped cobalt phosphide / carbon nanotube composite material according to claim 1, characterized in that: The mass ratio of Co3O4 / CNT to NaH2PO2 in step 2) is 1:
10.
4. A functionalized diaphragm modified with O-CoP / CNT prepared by the oxygen-doped cobalt phosphide / carbon nanotube composite material prepared by the preparation method of the oxygen-doped cobalt phosphide / carbon nanotube composite material according to claim 1, 2 or 3, characterized in that: The membrane substrate of the functionalized membrane is Celgard 2500, and the O-CoP / CNT composite material is coated on one side of the membrane substrate.
5. The O-CoP / CNT modified functionalized membrane according to claim 4, characterized in that: The preparation process of the functionalized membrane is as follows: O-CoP / CNT, conductive carbon, a binder and a solvent are dispersed to form a uniform slurry, wherein the mass ratio of O-CoP / CNT, conductive carbon and the binder is 8:1:1; the obtained slurry is uniformly coated on one side of a membrane substrate material by any one of spraying, blade coating or coating roller to form an O-CoP / CNT modified functionalized membrane, and then the coated membrane is vacuum dried at 50-60° C. to obtain an O-CoP / CNT modified functionalized membrane, wherein the conductive carbon is one or more of conductive carbon black, acetylene black, ketjen carbon and activated carbon, the binder is polyvinylidene fluoride PVDF, and the solvent is N-methylpyrrolidone NMP.
6. Use of the oxygen-doped cobalt phosphide / carbon nanotube composite material prepared by the method for preparing the oxygen-doped cobalt phosphide / carbon nanotube composite material according to claim 1, 2 or 3 in a lithium-sulfur battery.
Citation Information
Patent Citations
Liquid phase preparation method for carbon nano tube and cobalt oxide composite structure
CN101898134A
Block-shaped carrier nano-type alloy catalyst for carrying out alcoholysis on sodium borohydride to produce hydrogen and preparation method thereof
CN108479820A